NEW MEIR-KEELER TYPE QUADRUPLE FIXED POINT THEOREMS IN PARTIALLY ORDERED METRIC SPACES - ughade, manoj; Daheriya, R.D. (Journal of Global Research in Mathematical Archives(JGRMA), 2015)
In this article, we prove a number of quadruple fixed point theorems by usingÂ a generalization of Meir-Keeler type contraction. We introduce an example to illustrate the effectiveness of our results. Also an application, some results of integral type are given.